2015
DOI: 10.1016/j.ygcen.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of little skate (Leucoraja erinacea) recombinant transthyretin: Zinc-dependent 3,3′,5-triiodo-l-thyronine binding

Abstract: Transthyretin (TTR) diverged from an ancestral 5-hydroxyisourate hydrolase (HIUHase) by gene duplication at some early stage of chordate evolution. To clarify how TTR had participated in the thyroid system as an extracellular thyroid hormone (TH) binding protein, TH binding properties of recombinant little skate Leucoraja erinacea TTR was investigated. At the amino acid level, skate TTR showed 37-46% identities with the other vertebrate TTRs. Because the skate TTR had a unique histidine-rich segment in the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Secondly, Zinc is a micronutrient required for the biosynthesis of thyroid hormones, and Zn affects the activity of 5′-deiodinase for the conversion of T4 to triiodothyronine (T3) ( 44 , 45 ). In addition, Zn is necessary for the synthesis of TSH from pituitary and TRH from hypothalamus ( 46 , 47 ). Kralik et al ( 48 ) showed Zn to be required for the correct metabolism of thyroid hormone, and Zn deficiency might have a negative effect on the activity of normal thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Zinc is a micronutrient required for the biosynthesis of thyroid hormones, and Zn affects the activity of 5′-deiodinase for the conversion of T4 to triiodothyronine (T3) ( 44 , 45 ). In addition, Zn is necessary for the synthesis of TSH from pituitary and TRH from hypothalamus ( 46 , 47 ). Kralik et al ( 48 ) showed Zn to be required for the correct metabolism of thyroid hormone, and Zn deficiency might have a negative effect on the activity of normal thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an indispensable element in the functioning of 1,5′-deiodinase, which is necessary for the conversion of T 4 to T 3 [6]. Besides being required for the activity of thyroid hormones, zinc is essential for the synthesis of TSH from hypophysis and TRH from hypothalamus [7,21]. When the available information about the relation between zinc and thyroid is considered, changes in thyroid activity can be expected to result in variations in zinc levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the potential Chinese rare minnow (Gobiocypris rarus) transthyretin (CrmTTR) binding affinity of aromatic and aliphatic wastewater-derived DBPs was investigated by in vitro and in silico methods. The reasons why CrmTTR is selected are as follows: (a) transthyretin is one of the two thyroid hormone (TH) carrier proteins in fish, and previous studies had documented that the fish TTR could be disrupted by anthropogenic substances; (b) our previous study documented that aromatic DBPs were high-affinity hTTR disruptors . As the endocrine disrupting effects of compounds may be likely species-dependent, it is not clear whether the aromatic wastewater-derived DBPs are also potential disruptors of fish transthyretin or not.…”
Section: Introductionmentioning
confidence: 99%